The mosque in the Malay world: on the origins of spiritual form and space - Mohd Nawawi, Norwina; Jahn Kassim, Puteri Shireen; Hamat, Sufian (2019)
Man is created to submit only to the Almighty Allah SWT. Amidst daily routine and life challenges, Man's need for the spiritual nourishment of the soul to balance one's life need both physical and environmental support in keeping to the state of Taqwa through compulsory ritual daily and weekly prayers. Kusyuk or state of complete spiritual contemplation is what one’s seeks to achieve the balance. As such, the place and space for prayer or solat should not only be in a near distance from the workplace or home but with an environment that supports a momentary journey towards full contemplation or kusyuk. Islamic world includes cultures in the Far East. The spiritual basis of space and place in Mosque or Masjid, rather than the persistent hold of its Arab-Islamic origins in driving the notion of archetypes in Masjid design, necessitates a rethinking of what constitutes the fundamental. So, does the space and place for prayer in the form of masjid, surau, musolla in the Malay World support this innate function? This study thus explored masjid design in the Malay world from its vernacular origin to contemporary. The study analyses the quality of space and place of spiritual sanctuary amidst the daily living as an attempt to re-look into how the spiritual ethos of Islam was brought into masjid architecture in a physical form as the physical materialisation of the inherent values of Islam. The study reviewed the simplicity and austerity of the first Masjid in Islam - Masjid Nabawi as the masjid prototype that constitutes a more spiritually-linked framework linking Islam to the formative ideas and eventual compositions of masjid of the Malay world. The discourse had uncovered common principles that embrace the diversity and dialectic of the ummah of the Malay world in its identity and cultural expression to reflect intentions and predisposition that linked ultimately to spirituality. In this sense, the Masjid of the Malay world, either of vernacular origin or contemporary, in various degree, had embraced the fundamental principles of supporting spirituality in the house of Allah, but what about the Man, himself?